![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 390 - (x - 7) = 169 : 13
390 - (x - 7) = 13
x - 7 = 390 - 13
x - 7 = 377
x = 377 + 7
x = 384
b) ( x - 140 ) : 7 = 32 - 23 . 3
(x - 140) : 7 = -15
x - 140 = -15 . 7
x - 140 = -105
x = 105 + 140
x = 35
a) 390 - (x - 7) = 169 : 13
390 - (x - 7) = 13
x - 7 = 390 - 13 = 377
x = 377 + 7
x = 384
![](https://rs.olm.vn/images/avt/0.png?1311)
a,
13[x-9] = 169
=> x - 9 = 169/13
=> x - 9 = 13
=> x = 13+9
=> x = 22
b,
Viết lại đề:
7x+3 = 343
<=> 7x+3 = 73
=> x + 3 = 3
=> x = 3-3
=> x = 0
c,
230 + [16 + [x-5]] = 315 . 23
=> 230 + [16 + x - 5] = 315 . 8
=> 230 + 16 + x - 5 = 2520
=> 230 + 16 + x = 2520 + 5 = 2525
=> x = 2525 - 230 - 16 = 2279
d,
13.x - 32.x = 20171 - 12018
=> 13x - 9x = 2017 - 1
=> 4x = 2016
=> x = 504
a) 13 ( x-9 )=169
=> x-9 =169 : 13 =13
=> x=13+9 =22
b)\(7^{x+3}=343\)
\(7^x.7^3=343\)
\(7^x=343:7^3\)
\(7^x=1\Rightarrow x=1\)
c)230 + 16 +x -5 =315.8
241 +x =2520
x=2520-241=2279
d) 13x -\(3^2.x\)=2017-1
x(13-9)=2016
x.4=2016
x=2016:4
x=504
![](https://rs.olm.vn/images/avt/0.png?1311)
( x-6)^2 = 9
(x-6)^2=3^2
=>x-6=3
x=3+6
x=9
(2x-7)^2= 169
(2x-7)^2=13^2
=>2x-7=13
2x=13+7
2x=20
x=10:2
x=10
x^3 = 216
x^3=6^3
=>x=6
(x-6)^2=9
x-6^2=9
x-36=9
x=9+36
x=45
(2x-7)^2=169
2x-7^2=169
2x-49=169
2x=169+49
2x=218
x=218:2
x=109
x^3=216
x^3=6^3
=>x=6
tick cho mk nha bạn
![](https://rs.olm.vn/images/avt/0.png?1311)
a)390-(x-7)=169:13
<=>390-(x-7)=13
<=>x-7=390-13
<=>x-7=377
<=>x=377+7
<=>x=384
b)x-6:2-(48-24):2:6-3=0
<=>x-3-24:2:6-3=0
<=>x-6-12:6=0
<=>x-6-2=0
<=>x-8=0
<=>x=8
a) 390 - ( x - 7 ) = 169 : 13
390 - ( x - 7 ) = 13
x - 7 = 390 - 13
x - 7 = 377
x = 377 + 7
x = 384
b) x - 6 : 2 - ( 48 - 24 ) : 2 : 6 - 3 = 0
x - 3 - ( 48 - 24 ) : 2 : 6 = 0 + 3 = 3
x - 3 - ( 48 - 24 ) : 2 = 3 x 6 = 18
x - 3 - ( 48 - 24 ) = 18 x 2
x - 3 - 24 = 36
x - 3 = 36 + 24
x - 3 = 60
x = 60 + 3
x = 63
![](https://rs.olm.vn/images/avt/0.png?1311)
1) 2016 +x = 169x
<=> 2016 = 168x
<=> x=12
2) (26 - 3x) : 5= 4
<=> 26 - 3x = 20
<=> 3x =6
<=> x=2
3) x + 32 - 17 = 21
<=> x + 15 = 21
<=> x= 6
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : 1 + 3 + 5 + ..... + x = 1600
=> \(\frac{\text{[(x - 1) : 2 + 1](x + 1)}}{2}=1600\)
\(\Rightarrow\left(\frac{1}{2}x-\frac{1}{2}+1\right)\left(x+1\right)=3200\)
\(\Rightarrow\left(\frac{1}{2}x+\frac{1}{2}\right)\left(x+1\right)=3200\)
\(\Rightarrow\left(x+1\right)^2.\frac{1}{2}=3200\)
\(\Rightarrow\left(x+1\right)^2=6400\)
\(\Rightarrow x+1=80\)
=> x = 79